NALAR SANTRI: STUDI EPISTEMOLOGIS TRADISI DI PESANTREN - Muhammad war'i (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2019)
This paper discusses the reasoning of santri by using an epistemological approach to tradition in pesantren. With interpretive descriptive analysis techniques, the study points to several conclusions: First, the santri tradition leads to positive things such as: reading the yellow book, bahtsul masail, tarekat and barokah. Second, the tradition becomes an epistemological foundation in the acquisition of santri knowledge which can be mapped on four things, namely: bayani, burhani, irfani and wisdom. Meanwhile, santri's reasoning patterns take the form of compositions that enter each other where the aspects of bayani, burhani, irfani and wisdom are systematically formatted in the santri paradigm. Santri reasoning thus refers to intellectual professionalism and spiritual maturity. In turn, the students' reasoning will be very necessary in counter-understanding ideologies that are exclusively religious and state ideologies. In addition, the students' reasoning will provide a wealth of paradigm for someone to be open in seeing discourse, so that they tend to be inclusive. This fact will, in turn, play an important role in building a world of good communication media in cyberspace and social spaces in general.